Acute Oral Toxicity of the Supramolecular Complex Based on Albendazole and Triclabendazole (Altric-Extra) in Laboratory Outbred Mice and Rats - E. V. Lagereva; V. E. Abramov (Российский паразитологический журнал, 2020)
The purpose of the research is to evaluate the acute toxicity of Altric-Extra when introduced into the stomach to mice and rats.Materials and methods. The studies were conducted in the vivarium of the All-Russian Research Institute of Fundamental and Applied Parasitology of Animals and Plants. The acute toxicity of Altric-Extra was determined on 20 white outbred male mice weighing 19.3–23.3 g, 10 animals in a group and on 30 white outbred male rats weighing 150–196 g, 6 animals in a group. Altric-Extra was administered to mice of the experimental group once into the stomach in the form of a suspension in a dose of 5,986 mg/kg at the rate of 0.2 ml/10 g of body weight. Altric-Extra rats were also administered once into the stomach in the form of a suspension at the rate of 2.0 ml/100 g body weight. As a carrier in the preparation of the suspension, 1% starch gel was used. The experimental rats of groups 1, 2, 3 and 4 were given Altric-Extra at doses of 4,580.2 mg/kg, 3,846.2; 3,088.8 and 1,577.9 mg/ kg respectively. Mice and rats of the control groups were administered once with 1% starch gel. For 14 days, the behavior and condition of the animals was monitored. The body weight of the experimental animals was measured on the 1st, 3rd, 7th, 9th and 14th days of the experiment.Results and discussion. Medium lethal doses of LD50 have been established for oral administration to laboratory animals. For mice, the LD50 was more than 5 986 mg/kg, i.e., according to the generally accepted hygienic classification, Altrick-Extra belongs to hazard class 4 (low-hazard substances). On rats, the LD50 was 3 103.1±48.5 mg/kg (2,354.6÷3,851.5 mg/kg). Therefore, Altrik-Extra belongs to hazard class 3 (substances are moderately hazardous).